A study of illustration that promote Keretapi Tanah Melayu (KTM) in Malaysia from 1885 to 2018 / Zayanah Razalli - Razalli, Zayanah (2018)
Transport is a key requirement of human travel or movement from one place to another place without taking into account the distance to the destination. Keretapi Tanah Melayu (KTM) has provided invaluable services to the State. Various challenges have been made but the railways continue to move forward with the country's development. Until now the train is a service that still needed by the people and the State. This success is due to the strategy in promoting KTM itself. The way they campaign their names and the items they use to promote their names abroad. The purpose of this study is to study the illustration that use in promoting Keretapi Tanah Melayu (KTM) until they have reach their successful until now. This will have a further studies about the styles and types of illustrations that KTM had used. This study need to be done by doing the research through qualitative methods including interviews. It will be conducted by interview with the Executive Corporate Communication of KTM. As the results from this study, KTM has starts its biggest name with the used of illustrations as to promote the KTM itself but had decreased in the used of illustrations due to this modern age.